Locke's Theory of Demonstration and Demonstrative Morality1. (20th May 2018) - Connolly, Patrick J.
Abstract : Locke famously claimed that morality was capable of demonstration. But he also refused to provide a system of demonstrative morality. This paper addresses the mismatch between Locke's stated views and his actual philosophical practice. While Locke's claims about demonstrative morality have received a lot of attention it is rare to see them discussed in the context of his general theory of demonstration and his specific discussions of particular demonstrations. This paper explores Locke's general remarks about demonstration as well as his claims about demonstration in natural philosophy, mathematics, and morality. Careful attention to these detailed discussions motivates a reevaluation of Locke's views on demonstrative knowledge of morality. Specifically, while Locke did believe that some demonstrative moral knowledge might be in‐principle available to us he also believed that facts about the difficulty of demonstration meant that this knowledge would in‐practice be largely unattainable.